Survey and analysis for impact factors of psychological distress in HIV-infected pregnant women who continue pregnancy. (2nd October 2019) - Qin, Shouxue; Tan, Yanping; Lu, Bingyan; Cheng, Yuqing; Nong, Yanli
Abstract: Objective: The objective of this study is to explore the psychological distress of HIV-infected pregnant women who continue pregnancy, and analyze the possible influencing factors. Methods: A total of 194 HIV-infected pregnant women who continue pregnancy were enrolled for this study by a convenient sampling method during June 2012–August 2016. Participants completed questionnaires including Hospital Anxiety and Depression Scale (HADS), Berger HIV Stigma Scale (BHSS), Distress Thermometer (DT) and Problem List (PL), and to determine the cut-off value of DT in the group. Results: The positive detection rate of psychological distress in the HIV-infected pregnant women who continue pregnancy was 69.1%, and the highest frequency of PL was the emotional problems. The positive detection rate of anxiety was 60.8%, the positive detection rate of depression was 54.1%, and the discrimination score was 113.16 ± 19.21. Spearman relevant analysis showed that psychological distress score was positively correlated with anxiety, depression and discrimination score ( p < .001). Multiple linear regression analysis showed that relationship between husband and wife, family misfortune, Medicaid, chronic disease or high-risk pregnancy, viral load, CD4 + T cell count, infection and confidentiality could affect the psychological distress ( p < .05). The ideal cut-off value of DT in the group was 5. Conclusion: HIV-infected pregnant women who continue pregnancy have higher incidence of psychological distress, and the psychological distress is not inferior to cancer patients. The influencing factors are mainly related to the infection and pregnancy characteristics, and have nothing to do with the general social demographic characteristics. The DT can be used as a screening tool to quickly identify psychological distress of the group.